PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN TEKNIK PASANGAN TTW DI KELAS III SDN 18 - Rahmasari, Dea; Halidjah, Siti; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the using ttw pair technique to see improved the ability of write descriptive essays in class III State Elementary School 18 West Pontianak. The method used is descriptive method and form of Classroom Action Research is done collaboratevely. Classroom action research procedures include action planning, action implementation, action observation/observation, and reflection. The subjects of the study included grade III A with 25 students. Data collection techniques used are direct observation, direct communication, documentary studies, and measurements with observations sheet for students. This study was done 4 cycles, based on calculations by the percentage and the average grade of all cycles in a row, namely 40,8% in the first cycle becomes 56,8% in second cycle, becomes 77,5% in third cycle and finally becomes 88% in fourth cycle (last cycle). The ability of students in writing description essays has increased from first cycle to last cycle. In second cycle increased of 20%, in third cycle which increased of 26%, and so in last cycle has increased of 13%. This means there is an increased students ability of write descriptive essays using the ttw pair technique class III State Elementary School 18 West Pontianak.Keywords: Classroom Action Research, TTW Pair Technique, Writing Ability, Essay Description